Nursing care management in substitutive renal therapy in patients with COVID-19: integrative review - Cícero Damon Carvalho-de Alencar; Valéria de-Souza Araújo; Alves-Silva; Glauberto da-Silva Quirino; Antonio Germane Alves-Pinto (Sociedad Española de Enfermería Nefrológica, 2023)
Introducción: Among the systems most affected by COVID-19, the renal system stands out, which leads to challenges in the management of nursing care for these patients. Objective: To describe the scientific evidence on nursing care management in patients diagnosed with COVID-19 undergoing Renal Replacement Therapy. Methodology: Articles were searched in PubMed, SCOPUS, Web of Science, LILACS, BDENF, EMBASE, IBECS, CINAHL, COCHRANE LIBRARY, and Scielo databases, using the following cross-references: "renal therapy" AND "nursing care" AND "covid-19". To systematize the searches, the Boolean operator "AND" was used. Initially, 167 primary references were identified in the selected databases/virtual library, and as a final sample, 14 articles were included. Results: It was found that among the contributions to nursing care management in hemodialysis patient care in the context of the COVID-19 pandemic, the use of health technologies (examples: use of telehealth and the development of new protocols), development of new methods in nursing care management and continuing education are described in the literature. These tools were essential for the continuity of nursing care. Conclusion: Among the tools used for nursing care management in the context of the pandemic of COVID-19 in hemodialysis patients, health technologies and continuing education in health are included, enabling qualified care management.